Actual areas of improvement of regulatory and organizational support for the training of specialists with higher legal education at institutions of higher education of the system of the Ministry of Internal Affairs of Ukraine - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs)
The regulatory and organizational principles of reforming legal education at the current stage of the state’s development have been studied. The final content of the Concept of the Development of Legal Education, approved by the Committee of the Verkhovna Rada of Ukraine on Education, Science and Innovation, and the new editions of the standards of higher education in specialty 081 “Law” have been analyzed. Conceptual directions for the development of higher legal education have been formulated, taking into account the interests of the Ministry of Internal Affairs of Ukraine, and arguments have been also given regarding the preservation of relevant specialists training at higher education institutions of the Ministry of Internal Affairs of Ukraine.